Mangrove Planting, Climate Change Mitigation, Tahoa Village - Nirsal, Nirsal; Syafriadi, Syafriadi; Bantun, Suharsono (MEKONGGA: Jurnal Pengabdian Masyarakat, 2024)
and minimizing the impact of storms and waves that occur every year. This effort is carried out in a soft structure through mangrove planting. Apart from that, this activity also aims to strengthen the capacity of the Tahoa Village community regarding the importance of the mangrove ecosystem in protecting the coastal environment from storms and waves. The mangrove seeds selected were of the Rhizophora mucronata type. The choice of this type is based on the nature of this type of mangrove which is quite tolerant and adaptive to changes in environmental conditions. Apart from that, the selected mangrove seeds also have criteria that are ready for planting, including having a number of leaves ?4, being fertile, not diseased and not deformed/broken. The mangrove planting activity involved the Tahoa Village community and the Tahoa Village Mangrove Activist Group. Apart from that, this mangrove planting activity also involved the entire USN Kolaka Academic Community. The evaluation activity on the results of mangrove planting was carried out 2 months after the planting activity by taking into account several factors, including seedlings that might have broken roots during the transportation process from Kendari to Kolaka, as well as uncontrolled sea wave conditions. For this reason, mangrove replanting was carried out on several dead mangrove seedlings.